2017
DOI: 10.1371/journal.pone.0168550
|View full text |Cite
|
Sign up to set email alerts
|

Germline Genetic Variants in TEK, ANGPT1, ANGPT2, MMP9, FGF2 and VEGFA Are Associated with Pathologic Complete Response to Bevacizumab in Breast Cancer Patients

Abstract: BackgroundWe previously reported improved pathologic complete response (pCR) in a prospective phase II study using neoadjuvant bevacizumab in combination with chemotherapy compared to chemotherapy alone in breast cancer patients (41% vs. 25%, p = 0.0291). In this study, we queried germline single-nucleotide polymorphisms (SNPs) in angiogenesis-related genes for their impact on pCR and overall survival (OS).MethodsDNA for genotyping was available from 34 subjects who received bevacizumab in addition to chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…There have been multiple reports of increased levels of MMPs in breast cancer, and high expression of MMP-7 and MMP-9 has been reported to be associated with an unfavorable prognosis for patients with breast cancer (28)(29)(30). A meta-analysis also demonstrated that polymorphisms in the promoter regions of MMP-7 and MMP-9 may be associated with metastasis in breast cancer (31).…”
Section: Bcsc-1 Immunostaining [N (%)] ------------------------------mentioning
confidence: 99%
“…There have been multiple reports of increased levels of MMPs in breast cancer, and high expression of MMP-7 and MMP-9 has been reported to be associated with an unfavorable prognosis for patients with breast cancer (28)(29)(30). A meta-analysis also demonstrated that polymorphisms in the promoter regions of MMP-7 and MMP-9 may be associated with metastasis in breast cancer (31).…”
Section: Bcsc-1 Immunostaining [N (%)] ------------------------------mentioning
confidence: 99%
“…Previous studies indicated that TEK might be promising prognosis markers in cancers such as clear cell renal carcinoma (Nakashima et al 2019). TEK was reported to be associated with the complete response to bevacizumab in breast cancer patients (Makhoul et al 2017). TEK also could modulate the interaction of glioma and brain tumor stem cells, and promote an invasive phenotype (Liu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Another example was reported in metastatic CRC where VEGFA rs833061 and VEGFR1 rs9513070 respectively associated with the objective response rate and the OS in subjects treated with cytotoxic chemotherapy plus bevacizumab (Sohn et al, 2014 ). Analysis of genetic variants of other angiogenic-related genes in breast cancer using neoadjuvant bevacizumab in combination with chemotherapy compared to chemotherapy alone showed a correlation between specific SNPs in term of pathologic complete response but not in OS (Makhoul et al, 2017 ).…”
Section: Mechanisms Of Resistance To Anti-angiogenic Regimensmentioning
confidence: 99%